O corpo como mídia transformadora das relações humanas em instituição psiquiátrica - Oliveira, Alexandre Medeiros de (2009)
This Dissertation results from a theoretical-functional research based on experience of Cia. Dom Quixote featuring theater workshops at Hospital Nossa Senhora de Fátima da Congregação Irmãs Hospitaleiras do Sagrado Coração de Jesus from 2005 to 2007, as a volunteer activity performed with patients with mental disorders. The aim of such research was to analyze the communication processes which took place during theater workshops/performances, as well as to ponder over the outcome of such actions. To this end, we have used the body-medium theory suggested by Katz and Greiner (2005), the General Theory of Systems presented by Jorge de Albuquerque Vieira (2006, 2007 and 2008), as well as studies by neuroscientist António Damásio (1998, 2001 and 2003) and communications expert Muniz Sodré (2006) on perception and body processes concerning the body/environment meeting. We have also addressed studies of power established at institutions suggested by Michel Foucault (1968, 1987). The research methodology was based on mentioned authors bibliographic revision, aiming to have as an instrument the analyses of the accounts and reports produced by Cia. Dom Quixote members. The main issue was to discuss the very fine boundaries between artistic actions and therapy practice, using the in-depth study of the body as primary communication medium. Therefore, the research has established cooperation among diverse areas such as: communication, neuroscience, political and artistic theories, highlighting the importance of giving beyond disciplines to analyze complex phenomena where disciplinary procedures play a major role